Relation Between Anthropometric Muscle Mass Indicators and Lower Limbs Power in Talented Young Athletes [Relación Entre Indicadores Antropométricos Regionales de Masa Muscular y Potencia de Extremidades Inferiores en Deportistas Juveniles de Proyección] - Aedo-Munoz, E (Colegio Brasileiro de Ciencias do Esporte, 2018)
The purpose of this study was determined the level of relation between anthropometric segmental indicators of muscularity with the power levels expressed in the explosive and elastic strength, to carry it out 31 male athletes were (Age = 15.5 ±1.7 years; Weight = 61.4 ±11.5 kg) of diverse disciplines from the Program of National Sportive Projection of the Region of Aysén-Chile, were evaluated. The protocols of the ISAK for the anthropometric evaluations and Test of Bosco for the assessment of power of jump were followed. Results: An association between absolute power of the jumps SJ and CMJ and all the anthropometric variables of thigh (r > 0,8) it was able to establish a predictive model of the performance in jump by means of 3 anthropometric measurements has been established. © 2018 Colégio Brasileiro de Ciências do Esporte